Local Regulations on Religious Activities During the Pandemic from the Maqāṣid al-Sharī’ah Perspective: A Case in Sidoarjo, East Java - Hammis Syafaq; Nur Lailatul Musyafa'ah; Sri Wigati (Postgraduate Studies of Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2022)
Sidoarjo, during the Covid-19 pandemic, is one of the districts in East Java carrying large-scale restrictions (PSBB), because many Sidoarjo residents were exposed to Covid-19. For this reason, the Sidoarjo Government made a Regent’s Regulation on PSBB. Among the things that are restricted are religious activities. This has led to a limit in the implementation of worship for Sidoarjo residents. This article discusses the Sidoarjo regent’s regulations on restrictions on religious activities during the Covid-19 pandemic from the perspective of maqāṣid al-sharī’ah. This research is a library and qualitative research. The data was collected through a study of documents from Sidoarjo regency government regulations and analyzed by maqāṣid al-sharī’ah. Four regulations of the Regent of Sidoarjo related to religious activities during the Covid-19 pandemic Regulation Number 30, 32, 44 and 58 Tahun 2020. From the perspective of maqāṣid al-sharī’ah, religious activities were restricted during the Covid-19 pandemic to maintain religion and the soul. It is related to maintaining religion because the regulation does not prevent its citizens from worshipping even with strict health protocols. It is related to maintaining the soul because it aims to minimize the spread of Covid-19 in the Sidoarjo regency.